Impardonnables - Djian, Philippe 1949- (Gallimard, 2010)
Francis is a novelist. Tricky thing is, he hasn't written anything for 12 years, since his wife and daughter died. A relocation to the Basque area, and a new love interest, may break his writer's block -- however, his other daughter disappears, and Francis is beset by doubts over his new wife's fidelity. Perhaps this is not surprising since she had many affairs of many kinds before their marriage, but Francis himself is spending a good deal of time with a female friend whom he has known for years
Keywords: Novel; Writer's block / Fiction; Man-woman relationships / Fiction; Families / France / Pays Basque / Fiction; Pays Basque (France) / Fiction; Families; Man-woman relationships; Writer's block; France / Pays Basque; Popular literature; Fiction